A bibliometric analysis review of the Pennisetum (1970–2023) - Zhang, Yu; Li, Junqin; Wang, Xiangtao; Yang, Yuting; Zhou, Zijun; Deng, Xiaolin; Gao, Yang; Wang, Puchang (Frontiers in Sustainable Food Systems, 2024)
Pennisetum, a herbaceous plant belonging to the Poaceae family, is prevalent in tropical and subtropical regions and encompasses approximately 140 species. Its versatility is evidenced by its applications in forage, paper weaving, soil erosion control, and energy production. Current research on Pennisetum spans diverse fields including hay production, molecular breeding, and heavy metal absorption. However, this body of research is marked by redundancy, with a lack of clear focus. This article employs bibliometric methods to analyze the key research areas topics from 1970 to 2023. It also further discusses the future research direction of Pennisetum. Over the past five decades, research on Pennisetum has seen a significant increase, primarily concentrating on cultivation and breeding, ecological restoration, and industrial applications. These domains have become pivotal in advancing Pennisetum-related research. The paper also forecasts future innovations in Pennisetum research, focusing on molecular breeding, agricultural management, and novel material development. As a seminal contribution, this study offers a comprehensive graphical overview of Pennisetum research, establishing a foundational resource for ongoing scientific discourse.